2016
DOI: 10.1038/srep28066
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 protects tubular epithelial cells during injury via activation of ERK/MAPK signaling pathway

Abstract: Injury of renal tubular epithelial cells can induce acute renal failure and obstructive nephropathy. Previous studies have shown that administration of insulin-like growth factor-1 (IGF-1) ameliorates the renal injury in a mouse unilateral ureteral obstruction (UUO) model, whereas the underlying mechanisms are not completely understood. Here, we addressed this question. We found that the administration of IGF-1 significantly reduced the severity of the renal fibrosis in UUO. By analyzing purified renal epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
3
15
0
1
Order By: Relevance
“…Because we focused on histological and molecular changes of UUO kidney, we initially did not check the biochemical data such as BUN and serum creatinine level. However, many previous studies have reported that BUN and serum creatinine level was not significantly affected by only ipsilateral UUO due to the presence of a contralateral kidney with good renal function434445464748. Practically, we confirmed normal morphology and histology of contralateral kidney.…”
Section: Discussionsupporting
confidence: 79%
“…Because we focused on histological and molecular changes of UUO kidney, we initially did not check the biochemical data such as BUN and serum creatinine level. However, many previous studies have reported that BUN and serum creatinine level was not significantly affected by only ipsilateral UUO due to the presence of a contralateral kidney with good renal function434445464748. Practically, we confirmed normal morphology and histology of contralateral kidney.…”
Section: Discussionsupporting
confidence: 79%
“…The phosphorylation on these residues contributes to increased binding affinity of IGFBP-1 to IGF-1 (46). Non-phosphorylated IGFBP-1 has lower IGF-1 binding affinity and thus potentiates IGF-1R activation (8) which was also demonstrated to activate Erk (47,48). One explanation for the data presented here is that IGFBP-1 is expressed but not phosphorylated and therefore potentiates Erk activation in tamoxifen resistant breast cancer cells.…”
Section: Discussionmentioning
confidence: 64%
“…IGF-1 decreases following ischemic injury, and treatment with exogenous IGF-1 accelerates recovery by limiting cell apoptosis and promoting cell proliferation. 80,81 These findings were further confirmed by a study indicating that administration of rhIGF-1 2 h post injury suppresses the renal inflammatory response and upregulates EGF levels. 82 IGF-1 also promotes tubular regeneration after AKI by transactivating EGFR.…”
Section: Egf and The Egf Receptor In Akimentioning
confidence: 62%